KESEIMBANGAN INFRASTRUKTUR PENDIDIKAN TINGKAT SMP NEGERI DI KABUPATEN BANDUNG BARAT - Hilman Giat Lutfi Al-Ba (2017)
PendidikanmerupakansalahsatuupayapemerintahuntukmeningkatkankualitassumberdayamanusiasesuaiamanatdalampembukaanUndang-UndangDasar 1945 (UUD 1945) yaitumencerdaskankehidupanbangsa (UUD 1945).Infrastrukturpendidikanmerupakansalahsatusaranadanprasarana yang cukuppentingdalamsebuahperencanaankawasan. Hal inimengingatbahwapendidikanmerupakansalahsatukebutuhan yang wajibdipenuhiolehsetiapelemenmasyarakat, sehinggaperlunyamementingkankebutuhanluaslahanakansaranapendidikan yang sesuaidenganstandar yang telahditentukan. pembangunaninfrastrukturpendidikan yang padatahun 2011-2016 terjadipeningkatanjumlahgedungsekolahsebanyak 2 gedunguntuk. Rumusanmasalahpadapenelitianiniadalahbagaimanakebutuhaninfrastrukturpendidikan di Kabupaten Bandung Barat.Tujuanpenelitianiniadalahuntukmenghitungjumlahkebutuhaninfrastrukturpendidikan di Kabupaten Bandung Barat.Penelitianinimenggunakanmetodedeskriptifdenganjumlahsampeladalahseluruh SMP negeri di Kabupaten Bandung Barat yang berjumlah 62 sekolah.Jumlahsekolah SMP di KabupatenBandung Barat adalah 62 sekolah, sedangkankebutuhan SMP di Kabupaten Bandung Barat berjumlah 70 sekolah. Banyaklokasisekolah di kabupaten Bandung Barat berada di dekatdenganpemukimandanjalansehinggaketerjangkauansekolahtersebutsudahbaik;--- Education is one of the government's efforts to improve the quality of human resources as mandated in the launch of the 1945 Constitution (the 1945 Constitution) namely the intellectual life of the nation (UUD 1945). Infrastructure education is one of the important facilities and infrastructure in a regional planning. This is considering that education is one of the needs that must be fulfilled by every element of society, so the need to emphasize the need of land area will be educational facilities in accordance with predetermined standards.the development of educational infrastructure which in 2011-2016 increased the number of school buildings as much as 2 buildings for. The formulation of the problem in this research is how the education infrastructure needs in West Bandung regency. The purpose of this study is to calculate the amount of educational infrastructure needs in West Bandung regency. This research uses descriptive method with the total sample is all public junior high schools in West Bandung regency which amounted to 62 schools. The number of junior high schools in West Bandung regency is 62 schools, while the need for junior high schools in West Bandung regency amounts to 70 schools.Many school locations in West Bandung district are located close to the settlements and roads so that the affordability of the school is good.